La capa de ozono y su modificación por la actividad antropogénica: los huecos en las regiones polares - Banichevich, Antonio (1994)
There are exposed some characteristics of the absorption spectra of ozone and molecular oxygen. Singular properties of formation and destruction of ozone in the atmosphere are also exposed. and other important properties of this triatomic molecule. There are given some notions about heterogenic catalitic-chemical and dynamical processes which are considered to be the principal responsibles for the dramatic reduction in the production and regeneration of atmospherical ozone in the polar regions. There are described some geophysical (bariometry. orography and other microphysical properties) and photophysical-chemical characteristics of the polar regions, which transform the polar earth atmosphere in a storehouse, to where are transported and accumulated natural and anthropogenic substances by air masses transport.